2022
DOI: 10.1186/s12904-022-00963-y
|View full text |Cite|
|
Sign up to set email alerts
|

Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals

Abstract: Background Chronic illnesses and multi-morbidity can threaten competence and independence, particularly in old age. Autonomy becomes increasingly important in the context of sedation, as in this case medication leads to (further) changes of consciousness. The study aimed to identify possible age-related differences in the perspectives of healthcare professionals on patients’ autonomy, in the context of sedation in specialised palliative care. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Past research has found professionals' perceptions of dignity to depend on diverse factors, including their country of origin, medical specialty, clinical experience, religion, philosophy (Morita et al, 2015), patient age (Kurkowski et al, 2022), and culture (Butkevičienė et al, 2021). However, how they are embedded in specific care models has rarely been examined.…”
Section: Healthcare Professionals' Perceptions Of Eol Dignitymentioning
confidence: 99%
“…Past research has found professionals' perceptions of dignity to depend on diverse factors, including their country of origin, medical specialty, clinical experience, religion, philosophy (Morita et al, 2015), patient age (Kurkowski et al, 2022), and culture (Butkevičienė et al, 2021). However, how they are embedded in specific care models has rarely been examined.…”
Section: Healthcare Professionals' Perceptions Of Eol Dignitymentioning
confidence: 99%